(untitled) (Annual of the Faculty of Philosophy in Skopje, 2011)
Clinical experience and reseach demonstrate that no separate method or instrument can serve as a definitive indicator of posttrau- matic stress disorder. The multimodal method is advised as the most complete approach in the assessment of posttraumatic reactions. It represents a combination of structural interviews and self-report instruments with psychophysiological measures and collateral data. This model possesses the potential to surpass the psychometric limitations of each separate type of diagnostic instruments.